Relationship between Employees’ Job Outcomes, Workplace Environment, and Organizational Performance in a Pharmaceutical Industry in Pakistan - Javed, Nasir (2023)
Positive work attitude, work engagement, job satisfaction, job involvement, affective commitment, and intent to stay determine employees’ job outcomes. Employees’ job outcomes along with correct approach and positive role of workforce have a massive influence in an organization on how workforces accomplish targets and produce enormous outcomes resulting into organizational performance. However, these essential contributory elements of an organization’s success somehow lack in Pakistan’s pharmaceutical industry, which adversely affect overall performance of pharmaceutical companies. The current study intended at examining the relationship between employees’ job outcomes and organizational performance. Specifically, the study focused on mediating influence of the workplace environment on the said relationship in the context of Pakistan’s pharmaceutical industry. The impact of employees’ job outcomes on organizational performance has been a topic of much discussion and consideration that in what way positive work attitude, work engagement, job satisfaction, job involvement, affective commitment, and intent to stay persuade positive job outcomes from workforces. In the context of pharmaceutical industry, the subtleties of two essential elements “employees’ job outcomes” and “the workplace environment” perform an important part in modelling the fate of the pharmaceutical companies. The study adopted an optimistic prototype, which has led to an unprejudiced truth against those declarations matched and fact/ reality was determined. The study’s aim was to determine the design of reason and impact, which could envisage occurrence. The research has been conducted in line with the Social Exchange Theory, the Affective Events Theory, and the Resource-Based View Theory. Population of the study consisted of Pakistan’s pharmaceutical industry. Targeted population consisted of 52 pharmaceutical companies in Lahore Pakistan and the targeted respondents were employees of these companies working at different hierarchical levels. A quantitative research approach i.e., cross-sectional correlational design was followed to investigate the hypothesized relationships. 320 Survey questionnaires were distributed, and response of 254 targeted respondents were obtained, however 240 formed parts of the sample. The collected data was collated, and analyzed using SPSS v26 with Hayes’ PROCESS macro, and Mediation analysis was conducted using the bootstrapping method. As a result, this research study has yielded several significant insights. It contributes to the organizational performance literature by highlighting the influence of employees' job attitudes on organizational performance, with the workplace environment mediating this relationship. Additionally, it bridges gaps in current literature by integrating diverse theories, offering a more comprehensive understanding of these relationships. The study validates underpinning theories within the context of Pakistan’s pharmaceutical industry and provides actionable insights for enhancing organizational performance. Key drivers include management practices, a comprehensive workplace environment, effective communication, collaboration, technology, feedback mechanisms, and resource empowerment. Policymakers can use these findings to develop strategies for fostering employee’s job outcomes, and conducive workplace environments with a view to enhance organizational performance, especially within the pharmaceutical sector.